The Solicitor General and His Client - Wade H. McCree Jr. (Washington University Law Quarterly, 1981)
I will share with you a few thoughts on how the Solicitor General discharges his general statutory duty to "attend to the interests of the United States"' in the federal courts. More specifically, I would like to discuss how the Solicitor General gets along with his client-the United States-and how he ascertains the "interests" of that client.
Keywords: Administration of justice; United States. Department of Justice. Office of the Solicitor General; United States